2017
DOI: 10.1140/epjc/s10052-017-5377-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of polynomial Chaplygin gas warm inflation

Abstract: In the present work, we study the consequences of a recently proposed polynomial inflationary potential in the context of the generalized, modified, and generalized cosmic Chaplygin gas models. In addition, we consider dissipative effects by coupling the inflation field to radiation, i.e., the inflationary dynamics is studied in the warm inflation scenario. We take into account a general parametrization of the dissipative coefficient for describing the decay of the inflaton field into radiation. By studying th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…They studied the model for various types of Ω (dissipation parameter) and ξ (bulk parameter) and reported that the scalar spectral index (n s ) lies in the compatible range for less number of e-folds (N). The authors in [38] investigated the polynomial WI and confirmed the consistency of their results with recent astrophysical data. Sadjadi and Goodarzi [39] discussed oscillatory type of inflation with non-minimal kinetic coupling as a resolution of few number of e-folds ("non-minimal derivative coupling model [40]").…”
Section: Introductionsupporting
confidence: 63%
“…They studied the model for various types of Ω (dissipation parameter) and ξ (bulk parameter) and reported that the scalar spectral index (n s ) lies in the compatible range for less number of e-folds (N). The authors in [38] investigated the polynomial WI and confirmed the consistency of their results with recent astrophysical data. Sadjadi and Goodarzi [39] discussed oscillatory type of inflation with non-minimal kinetic coupling as a resolution of few number of e-folds ("non-minimal derivative coupling model [40]").…”
Section: Introductionsupporting
confidence: 63%
“…(36) and (37), then necessarily the dissipative coefficient should be given by expression (44). The dissipation coefficient for large √ ξφ can be approximated to…”
Section: The Weak Regimementioning
confidence: 99%
“…In the context of warm inflation, the generation of radiation remains quasi-stable, i.e., and , as derived in [26,27]. Therefore, under the slow-roll approximation, the equations of motion can be expressed as…”
Section: Introductionmentioning
confidence: 99%